Current implementation of third party certification in Malaysian eCommerce websites - Kasiran, Mohd Khairudin; Hassan, Syahida (2006)
Trust is an increasingly important concept on the Internet, especially for the eCommerce environment. Creating initial trust from buyer to seller is one of the problem that eCommerce need to address immediately since without this initial trust, buyers will be reluctant to commit any transaction through digital medium offered by eCommerce.This can be achieved by having Third Party Certification (TPC) displayed on their digital storefront as being point out by researches done in US and Europe.This paper presents the investigation result of the current implementation of TPC in Malaysian eCommerce websites.Information on how many sample Malaysian eCommerce website have TPC in the digital storefront, what are the TPC being used and what are the service provided by the TPC endorser, in order to understand the current trend of TPC in Malaysia. The output of this study can give an important background on the current implementation of TPC and be used as a basis of initial evaluation for business opportunity as a service provider for this kind of certification in Malaysia.